Lung microRNA deregulation associated with impaired alveolarization in rats after intrauterine growth restriction. - Pauline Dravet-Gounot (PLoS ONE, 2017)
Intrauterine growth restriction (IUGR) was recently described as an independent risk factor of bronchopulmonary dysplasia, the main respiratory sequelae of preterm birth. We previously showed impaired alveolarization in rat pups born with IUGR induced by a low-protein diet (LPD) during gestation. We conducted a genome-wide analysis of gene expression and found the involvement of several pathways such as cell adhesion. Here, we describe our unbiased microRNA (miRNA) profiling by microarray assay and validation by qPCR at postnatal days 10 and 21 (P10 and P21) in lungs of rat pups with LPD-induced lung-alveolarization disorder after IUGR. We identified 13 miRNAs with more than two-fold differential expression between control lungs and LPD-induced IUGR lungs. Validated and predicted target genes of these miRNAs were related to "tissue repair" at P10 and "cellular communication regulation" at P21. We predicted the deregulation of several genes associated with these pathways. Especially, E2F3, a transcription factor involved in cell cycle control, was expressed in developing alveoli, and its mRNA and protein levels were significantly increased at P21 after IUGR. Hence, IUGR affects the expression of selected miRNAs during lung alveolarization. These results provide a basis for deciphering the mechanistic contributions of IUGR to impaired alveolarization.